Influence of the process of damage accumulation on the asymptotic behavior of stress fields under creep conditions of a sample with a central crack - Yulia S. Bykova; Larisa V. Stepanova (Вестник Самарского университета: Естественнонаучная серия, 2023)
The present study describes the influence of the mutual effect of damage accumulation on the stress fields at the central crack tip in the plate subjected to uniaxial tension. The objective of the study is to analyze the cracked plate experiencing uniaxial loading under creep conditions using the CAE software SIMULIA ABAQUS taking into account the damage accumulation processes near the crack tip. Computations were performed by means of the user procedure UMAT (User material), which is based on the Bailey-Norton creep power law and the Kachanov — Rabotnov damage evolution equation describing the power-law damage accumulation processes. The analysis of the obtained results showed that in the creep and elasticity zones, in computations without taking into account the damage effect, there are asymptotics of stress fields that correspond to well-known analytical solutions of fracture mechanics (Hutchinson — Rice — Rosengren asymptotics for the creep zone, the asymptotics of linear fracture mechanics corresponding to the stress dependence. inversely proportional to the square root of the distance from the tip of the crack – for the zone of elastic behavior of the material. The presence of damage in the cracked specimen affected the asymptotic behavior of the crack tip fields. It is felt that the proposed procedure could pave the way for the analytical solution of the boundary value problem and allow us to determine the structure of the asymptotic solution of the problem. The finite element analysis clearly shows that the process of damage accumulation affects the change in the asymptotic behavior of the stress field in the vicinity of the crack tip and leads to a new asymptotic distribution of the stress tensor components. The proposed procedure can pave the way to an analytical solution of the boundary value problem and allow us to determine the structure of the asymptotic solution of the problem.